(untitled) (OODBODHAN, 2025)
In order to integrate two biologically relevant heterocycles—indole and pyrazole—a novel Schiff base, (E)-N-(2-(1H-indol-3-yl) ethyl)-1-(1-(4-chlorophenyl)-1H-pyrazol-4-yl) methanimine (IPM), was synthesized and thoroughly characterized. 1-(4-chlorophenyl)-1H-pyrazole-4-carbaldehyde and 2-(1H-indol-3-yl)ethan-1-amine underwent a condensation reaction to accomplish the synthesis, which produced IPM with 83% efficiency. The structure and purity of the compound have been confirmed through elemental analysis, mass spectrometry, FT-IR, UV-Vis, and NMR spectroscopy. The ¹H NMR spectrum revealed characteristic signals for the indole N–H, imine (C=N), aromatic protons, and ethyl linker. FT-IR analysis confirmed the presence of the azomethine linkage and characteristic vibrational modes of the aromatic systems. Indicative of prolonged conjugation between the indole, pyrazole, and imine units, UV-Vis spectroscopy revealed absorption bands corresponding to π-π* and n-π* transitions. The suggested molecular formula was supported by the ESI-MS spectrum, which showed a molecular ion peak at m/z 348.11 in addition to an isotopic pattern characteristic to chlorine. The successful synthesis and detailed characterization of IPM set the groundwork for future investigations into its potential applications in drug discovery and catalysis.